2017
DOI: 10.1016/j.jiph.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of antimicrobial resistance genes against Staphylococcus aureus isolates from Trinidad and Tobago

Abstract: Staphylococcus aureus continues to pose major public health challenges in many areas because of antibiotic resistance problems. In the Caribbean, especially Trinidad and Tobago, the challenge is not different. This study was performed to evaluate the antimicrobial resistance gene prevalence among S. aureus isolates in Trinidad and Tobago. Standard and molecular microbiological methods, including the Microscan automated system, DNA microarray and multi locus sequence typing (MLST) analysis, were performed on 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
6
22
0
Order By: Relevance
“…The phenotypic resistance in strains without the genes may be caused by other attributes, such as point mutations, biofilm formation, or antibiotic tolerance. The vanA and mefA genes were not detected in this study, and this is similar to previous reports [41].…”
Section: Discussionsupporting
confidence: 93%
“…The phenotypic resistance in strains without the genes may be caused by other attributes, such as point mutations, biofilm formation, or antibiotic tolerance. The vanA and mefA genes were not detected in this study, and this is similar to previous reports [41].…”
Section: Discussionsupporting
confidence: 93%
“…The MRSA isolates in the study were resistant to macrolides or macrolides/lincosamides and harbored ermA (n = 20), ermC (n = 2), and msrA (n = 17). 27 Schmitz et al reported that 93% of erythromycin resistant MRSA and 44% of erythromycin resistant MSSA, expression of macrolide-lincosamide-streptogramun B (MLS B ) resistance was constitutive, with ermA as predominant gene in European university hospitals. The ermA gene was more common in MRSA, while ermC was more common in MSSA isolates.…”
Section: Discussionmentioning
confidence: 99%
“…31 Akpaka et al reported that in MRSA strains, 20% harbored ant (4΄)-Ia gene. 34 Many reports from different parts of Asia such as Turkey (8%), 31 and India (9%) 34 have shown a low prevalence of the ant (4ʹ)-Ia gene. Likewise, in the current work, 14% of isolates were found to carry aph (3΄)-IIIa.…”
Section: Discussionmentioning
confidence: 99%